Pro Power BI Desktop - Aspin, Adam (Apress : Imprint: Apress, 2016)
This book shows how to deliver eye-catching Business Intelligence with Microsoft Power BI Desktop. You can now take data from virtually any source and use it to produce stunning dashboards and compelling reports that will seize your audience's attention. Slice and dice the data with remarkable ease then add metrics and KPIs to project the insights that create your competitive advantage. Make raw data into clear, accurate, and interactive information with Microsoft's free self-service business intelligence tool. Pro Power BI Desktop will help you to push your BI delivery to the next level. You'll learn to create great-looking visualizations and let your audience have fun by interacting with the elegant and visually arresting output that you can now deliver. You can choose from a wide range of built-in and third-party visualization types so that your message is always enhanced. You'll be able to deliver those results on the PC, on tablets, on smartphones, as well as share results via the cloud. Finally, this book helps you save time by preparing the underlying data correctly without needing an IT department to prepare it for you. Power BI Desktop will let your analyses speak for themselves. Simple techniques to make data into insight. Polished interactive dashboards to deliver attention-grabbing information. Visually arresting output on multiple devices grab the reader's attention.